Anthropology : the exploration of human diversity - Kottak, Conrad Phillip (New York : Random House, 1974)
Over the dozen or so semesters that I have taught Anthropology 101, a one-trimester introduction to general anthropology, at the University of Michigan, I have considered adopting one of the existing textbooks in the field. For various reasons, however, I never did. I have found most to be general anthropology cook-books, attempts to provide encyclopedias of anthropology more oriented toward anthropologists' data than toward the interests and organizing principles that hold the four sub-disciplines of anthropology together. Others, while less eclectic, seemed to forget the interests of contemporary college students, to supply an overabundance of detail, or to be written on a more advanced level than most beginners in anthropology appreciate. As I developed and modified my own course of forty-five lectures in introductory general anthropology, I found undergraduates receptive to my attempt to unify anthropology's subdisciplines through ecological and evolutionary principles. I wrote this book over about five semesters of Anthropology 101; the course improved the book, and the feedback on ideas and topics I was developing for the book improved the course.
The Study of Man -- The Evolution of man through the Beginning of Food Production -- Culture, Race, and Language -- Sociocultural Adaptive Means -- The End of the Primitive World and the Contemporary Relevance of Anthropology.
Includes bibliographical references and index.
Keywords: ANTHROPOLOGY